DOI: 10.11606/d.7.2006.tde-17102006-123438
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de assistência de enfermagem: identificação e análise em instituição hospitalar de ensino.

Abstract: À professora Valéria Castilho pela pertinência das sugestões no exame de qualificação e dúvidas sanadas ao longo do caminho. À Luciana HM. Cabral e Tarcísia L. Brogna pela valiosa contribuição na coleta de dados, de forma responsável e coerente, os meus sinceros agradecimentos. Ao Raul Gaidzinski, pelas orientações estatísticas. Á Maria Eduarda, pela disponibilidade na correção de português na última hora. À Karina, Daniela e Diley pelo auxílio na formatação, dicas e ensinamentos de informática. À Jane Prado, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
6

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 5 publications
(5 reference statements)
3
14
1
6
Order By: Relevance
“…The results appointed in this research regarding the percentage distribution of mean staff numbers among the nursing team categories support other researchers' (15,17) findings, who previously demonstrated that the proportion of care hours attributed to nurses at Brazilian health institutions is lower than that attributed to nursing auxiliaries and technicians, and that they remain very distant from current COFEN recommendations.…”
Section: Discussionsupporting
confidence: 86%
“…The results appointed in this research regarding the percentage distribution of mean staff numbers among the nursing team categories support other researchers' (15,17) findings, who previously demonstrated that the proportion of care hours attributed to nurses at Brazilian health institutions is lower than that attributed to nursing auxiliaries and technicians, and that they remain very distant from current COFEN recommendations.…”
Section: Discussionsupporting
confidence: 86%
“…Studies involving nursing professionals have evidenced similar results, calling attention to the high frequency of absences, motivated by sick leave, in different hospital units (7)(8)(9) . Based on these concerns, the following theoretical premise is outline to guide this research: the nursing work process allows for the workers' interaction with workloads that produce different exhaustion processes and imply the worker's absence from work.…”
Section: Introductionmentioning
confidence: 66%
“…These results are different from both the HU-USP (5) and Hospital São Paulo (11) studies, where there was no overall predominant type of absence for this group of workers at the studied units. However, a later investigation performed at HU-USP (14) verified that the percentage of unplanned absences due to INSS-related leaves for this category was very significant, which shows the importance of monitoring this variable at the institutions.…”
Section: Unplanned Absencesmentioning
confidence: 95%
“…At the same institution, in a five-year period, the percentages varied from 0.2% to 13.5% for nurses, and from 0.9% to 21.9% for technicians/auxiliaries (14) . At medical and surgical hospitalization units of a hospital in western Paraná, the percentage of these absences varied from 6.9% to 9.7% for nurses and from 6.2% to 11.4% for technicians/auxiliaries (10) ; At Hospital São Paulo, located in the city of São Paulo, the variation of these percentages in 40 hospitalization units ranged from 0.5% to 15.7% for nurses, and 0.7% to 12.4% for technicians/auxiliaries (11) .…”
Section: Unplanned Absencesmentioning
confidence: 99%
See 1 more Smart Citation